Pestilence, Sword and Famine Biblical Reflections on the Pandemic - Lefebvre, Philippe 1960- (2022)
The bible mentions the great scourges that strike humanity, even using the Greek language of the pandemic. Disasters are moments in which forms of sociability are rearranged and in which unexpected figures appear with new ideas. In times of crisis Noah's ark or the sanctuary in the desert provide alternative sites where the word circulates. Christ sets the gift of his person within a "pandemic" reversal that reaches as far as the ends of the earth.
Keywords: COVID-19 pandemic; Disasters; Greek Language